Six suspects - "Swarup,Vikas" (London, 2008)
The basis for The Great Indian Murder, now a streaming series!Seven years ago, Vivek "Vicky" Rai, the playboy son of the home minister of Uttar Pradesh, murdered bartender Ruby Gill at a trendy restaurant in New Delhi, simply because she refused to serve him a drink. Now Vicky Rai has been killed at the party he was throwing to celebrate his acquittal. Swarup unravels the lives and motives of the six suspects, offering both a riveting page-turner and an insightful look into the heart of contemporary India.
Keywords: English Fiction